Plan de negocios para la factibilidad de una comercializadora de café en el municipio de Moniquirá, Boyacá - Restrepo Briceño, Oscar Rubiel; Rodríguez Sánchez, Jhon Sneider (Universidad Antonio Nariño, 2023)
Recognizing coffee as a product in great demand in the country is important to start this project, because the idea arises from the need to give added value to traditional coffee through a selection of the best quality grain. This shall be ensured